Development and testing of a cleaner cum grader for black pepper - JAMES P. GEORGE MUNEER K SHARMILA MATHEW; Er. Prince M. V (Guide) (Tavanur 1998 Department of Post Harvest Technology& Agricultural Processing)
the cleaning and grading operations of black pepper are now concentrated at the wholesalers and the exporters level and are carried out through highly sophisticated vibrators and separators.
Development and testing of a cleaner cum grader for black pepper